Implementation Of The Law Against Playing Victims Who Harm The Police Institution (Case Study Of Percut Sei Tuan Police Station): Implementation Of The Law Against Playing Victims Who Harm The Police Institution (Case Study Of Percut Sei Tuan Police Station) - Sugih Ayu Pratitis; ⁠Muslim Harahap; Dearma Sinaga; Mhd. Ansor Lubis; Gerald Elisa Munthe (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This research aims to find out about legal regulations related to playing victims who cause harm to other parties, to find out the steps taken by POLRI in dealing with playing victims, and to analyze cases of spreading hoax news by playing victims at Percut Sei Tuan Police Station. By using empirical legal research methods, this research examines the problem by taking examples of real cases that have occurred in the community. Empirical legal research methods study law as actual behavior and unwritten social phenomena, which occur in the midst of community life. Therefore, empirical legal research is also known as sociological legal research. The results showed that positive law in Indonesia does not provide a detailed explanation of the sanctions for playing victim. Such actions can have serious implications and can be punished by various articles in the Criminal Code, for example Article 311 of the Criminal Code, Article 378 of the Criminal Code, and others. The handling of perpetrators who pretend to be victims or known as “playing victim” is part of the responsibility of the National Police in maintaining public order and security.